Revisiting The Marketing Mix In Digital Telecommunications: Analyzing The Factors Of Sales Instability In By.U Surabaya - Assyaffa Maulida; Budi Prabowo (Jurnal Investasi Islam, 2026)
This research aims to analyze the 4P marketing mix strategy in increasing the sales of by.U starter packs at PT Telekomunikasi Selular Surabaya. The research gap is identified through the phenomenon of unstable sales volume fluctuations and a significant decline in 2025, despite by.U’s implementation of an innovative digital telco concept targeting the youth segment. The methodology employed is descriptive research with a qualitative approach. Data were collected through in-depth interviews with management, direct sales staff, and consumers, supplemented by observation and documentation. Analysis was conducted using the interactive model and the evaluation of Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices within a  SWOT framework. Key empirical findings indicate that  the company’s strategic position lies in Quadrant I (Aggressive) with coordinate (1,60;1,37), signifying substantial internal strength to capture expansive digital market opportunities. The “Life On” product feature (no active period) and community-based promotional strategies, such as by.U Goes to School/Campus, proved to be critical factors in attracting purchasing interest. The novelty of this research lies in its in-depth analysis of the performance of Indonesia’s first end-to-end digital mobile service in facing the urban market saturation phase between 2019 and 2025. The practical contribution provided is a recommendation to strengthen customer retention strategies through specialized loyalty programs (renewal) and technical application performance improvements to maintain consistent sales stability amidst intense industrial competition.